China - rise to economic power - Černochová, Veronika (2015)
Regarding the increasing influence of People's Republic of China on the world markets, this thesis studies its economic development leading to its success and firm position in today's international trade. The historical economic development is described paying special attention to the trade reforms, which came into force at the end of 1970s and the beginning of 1980s. Consequently, the membership in the World Trade Organization and the crucial factors supporting the quick increase of the country's importance are described in more detail, specifically the labour, natural resources, exchange rate policy, human capital and savings and investments. Detailed analysis of the current commodity and territory structure of the People's Republic's of China international trade is provided, followed by information about the development of its position among its world competitors. Also, its competitiveness is evaluated, focusing on both strong and weak parts of the economy.